Autofluorescent Artemisinin-Benzimidazole Hybrids via Organo-Click Reaction: Study of Antiviral Properties and Mode of Action in Living Cells - Herrmann, Lars; Hahn, Friedrich; Grau, Benedikt; Wild, Markus; Niesar, Aischa; Wangen, Christina; Kataev, Evgeny; Marschall, Manfred; Tsogoeva, Svetlana (Chemistry - A European Journal, 2023)
Drug modification by a fluorescent label is a common tool for studying its mechanism of action with fluorescence microscopy techniques. However, the attachment of a fluorescent label can significantly alter the polarity, solubility, and biological activity of the investigated drug, and, as a result, the studied mechanism of action can be misrepresented. Therefore, developing efficient drugs, which are inherently fluorescent and can be tracked directly in the cell is highly favorable. Here an easy formation of fluorescent hybrid drugs is presented, generated by a combination of two readily available non-fluorescent pharmacophores via a non-cleavable linker using a Ramachary-Bressy-Wang organocatalyzed azide-carbonyl [3+2] cycloaddition (organo-click) reaction. All newly prepared fluorescent compounds showed strong anti-HCMV activity (EC50 down to 0.07±0.00 μM), thus presenting a very promising drug developmental basis compared to the approved drug ganciclovir (EC50 2.60±0.50 μM). Remarkably, in vitro fluorescent imaging investigation of new compounds revealed induced changes in mitochondrial structures, which is a phenotypical hallmark of antiviral activity. This approach opens up new vistas for the easy formation of potent fluorescent drugs from readily available non-fluorescent parent compounds and might facilitate insight into their mode of action in living cells, avoiding the requirement of linkage to external fluorescent markers.
CRIS-Team Scopus Importer:2023-09-08
Keywords: artemisinin-benzimidazole hybrids; autofluorescent antivirals; confocal microscopy; organo-click reaction; [3+2] cycloaddition